2015
DOI: 10.1007/s10719-015-9593-7
|View full text |Cite
|
Sign up to set email alerts
|

Cellular metabolism of unnatural sialic acid precursors

Abstract: Carbohydrates, in addition to their metabolic functions, serve important roles as receptors, ligands, and structural molecules for diverse biological processes. Insight into carbohydrate biology and mechanisms has been aided by metabolic oligosaccharide engineering (MOE). In MOE, unnatural carbohydrate analogs with novel functional groups are incorporated into cellular glycoconjugates and used to probe biological systems. While MOE has expanded knowledge of carbohydrate biology, limited metabolism of unnatural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 44 publications
3
49
0
1
Order By: Relevance
“…Sarcoma 180 cell line was cultured in RPMI 1640 medium [ 20 ] containing 10% fetal bovine serum, 200 U/ml penicillin, and 200 μg/ml streptomycin at 37 °C, 5% CO 2 in humidified incubator.…”
Section: Methodsmentioning
confidence: 99%
“…Sarcoma 180 cell line was cultured in RPMI 1640 medium [ 20 ] containing 10% fetal bovine serum, 200 U/ml penicillin, and 200 μg/ml streptomycin at 37 °C, 5% CO 2 in humidified incubator.…”
Section: Methodsmentioning
confidence: 99%
“…Although mannosamine derivatives are relatively well tolerated by many cell lines (Almaraz et al 2012;Keppler et al 2001;Pham et al 2015), high concentrations may be cytotoxic for susceptible cell types such as neurons (Almaraz et al 2012;Du et al 2009). Mature (day 5, d5) 1 3 LUHMES cells were exposed to increasing concentration of the peracetylated sugars Ac 4 ManNAc and Ac 4 ManNAz for 24 h. Both, the neurite integrity and number of viable cells was measured and concentrations of ≥ 20 µM were found to be cytotoxic (Fig.…”
Section: Use Of Mge For Incorporation Of Labeled Sia Into Cell Surfacmentioning
confidence: 99%
“…used MOE to introduce azide‐containing glycoproteins into cell surface using N ‐azidoacetylmannosamine (ManNAz) as a biosynthetic precursor . Based on the studies of Kohler and others, the metabolic efficiency of different unnatural sialic acid precursors was cell line‐dependent for promiscuous intracellular environments . Some experiments demonstrated that K562, SH‐SY, HeLa and PC‐3 cells were almost unable to metabolize some unnatural modified mannosamine analogs to membrane sialic acid glycoconjugates.…”
Section: Tools To Probe Siglecsmentioning
confidence: 99%